Pembuatan Selulosa Asetat Dari Molase: Pembuatan Selulosa Asetat Dari Molase - Teguh Gustiansyah; Dewi Astuti Herawati (Program Studi S1 Teknik Kimia, Fakultas Teknik, Universitas Setia Budi, 2022)
Previous research stated that cellulose acetate is made from wood containing cellulose. This research utilizes molasses as a producer of cellulose from nata de molasses. Nata de molasses is then acetylated to produce cellulose acetate. The aim of the study was to determine the effect of molasses content on acetyl content and degree of substitution of cellulose acetate. The manufacture of cellulose acetate goes through 3 stages, namely making nata de molasses, pollinating nata de molasses, and making cellulose acetate. Making Nata de molasses using molasses as much as 1000 ml with molasses levels: 0.5%, 1%, and 1.5%. Nata de molasses is dried and then blended to a size of 40 mesh and produces nata de molasses powder. Nata de molasses powder was hydrolyzed using glacial acetic acid, then anhydrous acetic acid and sulfuric acid were added as catalysts for the acetylation process. After the acetylation process is complete, the cellulose acetate powder is purified and then dried. In this study, the nata de molasses produced had -cellulose content of 85.46% - 88.75%. The results showed that cellulose acetate from 1.5% molasses had the characteristics of cellulose acetate as a plastic making material with an acetyl content of 29.55854% and a substitution degree of 1.56561. Abstrak Penelitian terdahulu menyatakan bahwa Selulosa asetat dibuat dari bahan kayu mengandung selulosa Penelitian ini memanfaatkan molase sebagai penghasil selulosa dari nata de molase. Nata de molase kemudian diasetilasi menghasilkan selulosa asetat. Tujuan penelitian adalah mengetahui pengaruh kadar molase terhadap kadar asetil dan derajat substitusi selulosa asetat. Pembuatan selulosa asetat melalui 3 tahap yaitu pembuatan nata de molase, pembuatan serbuk nata de molase, dan pembuatan selulosa asetat. Pembuatan Nata de molase menggunakan molase sebanyak 1000 ml dengan kadar molase: 0,5%, 1%, dan 1,5%. Nata de molase dikeringkan kemudian diblender hingga ukuran 40 mesh dan menghasilkan serbuk nata de molase. Serbuk nata de molase dihidrolisis menggunakan asam asetat glasial, kemudian ditambahkan asam asetat anhidrat dan asam sulfat sebagai katalis untuk proses asetilasi. Setelah proses asetilasi selesai serbuk selulosa asetat dimurnikan lalu dikeringkan. Pada penelitian ini nata de molase yang dihasilkan memiliki kadar -selulosa sebesar 85,46% - 88,75%. Hasil penelitian menunjukkan selulosa asetat dari molase 1,5 % mempunyai karakteristik selulosa asetat sebagai bahan pembuatan plastik dengan kadar asetil 29,55854% dan derajat subtitusi sebesar 1,56561